Designing Website Application as An Academic and Non-Academic Assistive Tool for Students with Slow Learner - Devanny Gumulya; Kristian Harijadi (Jurnal Desain Indonesia., 2021)
The COVID-19 pandemic has resulted in PSBB (Large-Scale Social Restrictions) regulations that affect all aspects of life, one of which is the education sector. Changes in the education system that have occurred significantly have many schools and are not running smoothly. In this case, the percentage will be even greater for students with special needs, especially students who are included in Slow Learner. The purpose of this research is to innovate in the development of assistive technology, improve the learning experience for students with special needs. The research result is a website application named Temaninklusi is a website application design proposal for lecture to create digital pictorial card as a additional learning material for Slow Learner at University level, as pictorial card has been proven as an effective tool to assist reading comprehension since early age. The website application also connects lecture, mentor and counselor to help slow learner adjusting their academic life.